2019
DOI: 10.1111/resp.13478
|View full text |Cite
|
Sign up to set email alerts
|

BMI but not central obesity predisposes to airway closure during bronchoconstriction

Abstract: Background and objective: Obesity produces restrictive effects on lung function. We previously reported that obese patients with asthma exhibit a propensity towards small airway closure during methacholine challenge which improved with weight loss. We hypothesized that increased abdominal adiposity, a key contributor to the restrictive effects of obesity on the lung, mediates this response. This study investigates the effect of body mass index (BMI) versus waist circumference (WC) on spirometric lung function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
1
24
0
1
Order By: Relevance
“…Interestingly, they found that waist circumference was closely related to restrictive spirometry changes, with reductions in FEV 1 and FVC, but was not related to the closing index. However, BMI was associated with an increased FVC . Using multivariate analysis, the closing index was related to BMI but not waist circumference.…”
Section: Obesity and Asthmamentioning
confidence: 82%
See 1 more Smart Citation
“…Interestingly, they found that waist circumference was closely related to restrictive spirometry changes, with reductions in FEV 1 and FVC, but was not related to the closing index. However, BMI was associated with an increased FVC . Using multivariate analysis, the closing index was related to BMI but not waist circumference.…”
Section: Obesity and Asthmamentioning
confidence: 82%
“…Using this large cohort, they demonstrated that, with multivariate regression, both increasing age and obesity were associated with an increased closing index. To further define this mechanism, the investigators assessed the closing index and how this was related to body mass index (BMI) and waist circumference in a new study of 116 patients with asthma . Interestingly, they found that waist circumference was closely related to restrictive spirometry changes, with reductions in FEV 1 and FVC, but was not related to the closing index.…”
Section: Obesity and Asthmamentioning
confidence: 99%
“…The findings of Peters et al therefore add important understanding to an area that is poorly understood and will hopefully stimulate further research into mechanisms that explain the problems of obesity in asthma that continue to face clinicians in their everyday practice.…”
mentioning
confidence: 81%
“…Compared with the knowledge of how obesity affects normal airways, less is known about how obesity affects asthmatic airways. Hence, the recently published study of asthmatic patients by Peters et al in Respirology , as well as previous publications from this group, is important in this regard. Their finding that obesity has minimal to no effect on sensitivity to bronchoconstriction is consistent with published data.…”
mentioning
confidence: 94%
“…Obesity will cause extrathoracic restriction and is reported to promote airway hyperresponsiveness, most likely via increased airway closure [10]. This is related to obesity but not waist circumference [11], suggesting the effects might not simply be due to poor inspiratory effort due to diaphragmatic splinting but could be due to additional factors. Several studies have demonstrated that weight reduction by diet and exercise or bariatric surgery improve asthma outcomes, including symptoms, airway hyperresponsiveness and exacerbation frequency [12][13][14][15].…”
mentioning
confidence: 99%